Democratic Republic of Sao Tome and Principe : Request for a 40-month Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2019)
Sao Tome and Principe is a fragile, small island-state, with limited resources and capacity. The last Extended Credit Facility (ECF) arrangement expired at end-2018 having gone off-track amid parliamentary elections, power outages, internal and external imbalances, and high debt vulnerability. Growth slowed, inflation rose, the fiscal position deteriorated, and foreign reserves declined sharply in 2018, while some critical structural reforms were delayed. Higher and more inclusive growth is needed to reduce poverty and unemployment, particularly among the large youth population.